"People and Government Travelling Together": Community Organization, Urban Planning and the Politics of Post-War Reconstruction in Toronto 1943–1953 - Brushett, Kevin (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1999)
Most histories of urban planning, urban politics, and the development of the welfare state have largely neglected both the existence and the importance of citizen participation in any period prior to the 1960s. The establishment of the Toronto Reconstruction Council/Civic Advisory Council in 1943, and the Community Council Coordinating Committee (4C's) in 1947, however, illustrates the importance of popular involvement in city and social planning during a crucial period in the history of Toronto and Canada as a whole. Organized by the local state both the Reconstruction Council and the 4C's tried to harness the tremendous surge of local activism and social idealism engendered by Torontonians' own attempts to tackle the social problems caused by a decade and a half of depression and war, as well as by their hopes for post-war reconstruction. Intended in many ways to manufacture consent for civic reconstruction plans, the agenda of these two organizations was often captive to the demands made by ordinary Torontonians out of necessity and self-interest.This article examines Toronto's unique experiment to harness citizen and community participation in aid of social and urban planning schemes. It argues that the rise and subsequent fall of the community organization movement represented a crucial turning point turning in citizen participation in urban planning politics. The formation of the TRC/CAC and the 4Cs represented a plastic moment in Toronto urban planning politics when the ideals of local democracy and citizen participation seemed achievable. However, the community organization movement foundered on the very divisions it hoped to overcome: class, ethnicity, and most importantly political. Ultimately the failure of these two organizations to incorporate genuine citizen participation in social and urban planning schemes, as the case of the Regent Park slum clearance and public housing project illustrates, haunted city planning politics for the next two decades.